Information Needs and Role of Libraries for Transgender Students in Higher Education: A Case Study of Pakistan - Saima Hanif; Qurat Ul Ain Saleem; Nazia Wahid; Murtaza Ashiq (Malaysian Journal of Library and Information Science, 2025)
This study explores the everyday information needs and role of university libraries in informing education administrators and policymakers to provide more library facilities for the inclusion of transgender students. A qualitative research approach was employed to meet the objectives of this study. Interviews were conducted using a semi-structured interview guide and a snowball sampling technique was adopted to access the transgender community. The results highlighted that the information need of transgender community revolves around community issues, health, fashion, job searching, and safety. It is observed that they usually use online sources such as Google, official websites, and social media-based networking sites (Facebook, WhatsApp, Instagram) to fulfill their information needs. The participants were of the view that library services need improvements, and should create more inclusive and accessible resources. This study has its own theoretical, policy, and practical implications in terms of demanding existing theories to be expanded about how different social groups search for their unique information needs. This study also supports the idea that libraries need a serious and rapid revaluation of their services, moreover, immediate support is needed for transgender students by both educational institutions and policymakers.